1999
DOI: 10.1177/003693309904400208
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Nurse Practitioner on Out of Hours Work Intensity for Surgical House Officers

Abstract: We have prospectively studied the influence of a nurse practitioner service on out of hours work intensity of surgical house officers. Data collection was achieved by prospective audit. The study was set in the surgical wards in a large teaching hospital. The main outcome measures were; 1) the nature and frequency of overnight calls to the nurse practitioner, and 2) the outcome of these calls (doctor not bleeped, telephone advice given by doctor or doctor attended ward). A total of 645 calls were made over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…2,3,14,15,21,23,27,30,31 It is important that we critically examine the effect that these changes have on the hospital work environment, and most importantly on patient care, before advocating widespread adoption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3,14,15,21,23,27,30,31 It is important that we critically examine the effect that these changes have on the hospital work environment, and most importantly on patient care, before advocating widespread adoption.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,[19][20][21][22][23][24][25] The main effects documented included a decrease in overall resident work hours, increased operating room time, reduced number of pages, increased time for educational activities and increased sleep time. Victorino and Organ 22 demonstrated decreased resident workload and stress levels and improved resident morale after the addition of PEs.…”
Section: Effect On Residentsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 NPPs in surgery particularly are valuable in allowing residents operating room time. Studies have shown that NPPs decrease the workload of residents, 6,7 while providing benefits to patients and hospitals, including a shortened length of stay. 8,9 The Mount Sinai Surgical Residency program in New York City is currently composed of 72 residents.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies however studied the effects of the use of nurses for the telephone triage or telephone consultations [34,35]. Others, studied the effects of the use of NPs in a hospital setting [36,37] and the effectiveness of emergency care practitioners (ECP) in a primary care out of hours service [38,39]. Nevertheless, it is unknown if nurse practitioners are also useful to perform face to face consultations in a primary out of hours setting.…”
Section: Discussionmentioning
confidence: 99%